Optimization of the Protocol for Isolation of Exosome and Secretome of CACO-2 Colorectal Adenocarcinoma Cells from Conditioned Media for Subsequent Mass Spectrometric Analysis - Shushkova, N.A.; Novikova, S.E.; Farafonova, T.E.; Zgoda, V.G. (Biomedical Chemistry: Research and Methods, 2020)
The conditioned media in which the tumor cells are cultured represents a model object for studying of secretome and proteomic composition of exosomes. This pool of proteins is of particular interest in terms of the search for potential markers of malignant diseases. The efficiency of the isolation of exosomes and secretome from the cell culture media largely determines the success of their analysis by the mass spectrometric method. In this paper, we have applied various approaches to isolate secretome and exosomes originated from Caco-2 colorectal adenocarcinoma cells. The combination of ultrafiltration and centrifugation provided a deep proteomic analysis of the secretome and exosomes obtained from the one initial volume of conditioned medium without the addition of fetal bovine serum. Applying tandem mass spectrometric analysis we have identified 436 secreted proteins. In exosomes, the characteristic proteins ALIX, CD63, syntenin, lactadherin (MFGE8) were identified. Using targeted mass spectrometry, the exosome markers CD82, CD9 and HSPA8 were determined at the levels of 0.08 ± 0.03 fmol/μg, 0.13 ± 0.03 fmol/μg and 2.6 ± 0.02 fmol/μg of total protein, respectively. Among the secreted proteins, there were many markers associated with tumor progression and metastasis, such as DAG1, PODXL, LRRN4, TGFBI, IL6ST, DSC1, DSG1, and NPC2.